Effect of process variables in the production of fried green plantain in vacuum - CHAVEZ-SALAZAR, Andres; CASTELLANOS-GALEANO, Francisco J.; MARTINEZ-HERNANDEZ, Lorenzo J. (Vitae, 2017)
Background: This article technology deep frying green plantain was evaluated. Objectives: To optimize the process of deep frying in the production of green banana slices and set the association in terms of the quality parameter: texture; from the point of sensory and instrumental view. Methods: Was used as a raw material banana green maturity, variety (Dominico Harton) and a mixture of refined vegetable oils from soybeans and palm olein with antioxidant (TBHQ). For the evaluation of the process we worked with various pressure ranges, driving force (∆T) and time; selecting maximum and minimum for these process variables (10-79kPa) values (13-113°C) and (57-663s) respectively. For the analysis of the response variables (moisture content, fat content and texture “hardness”) officially sanctioned AOAC methods and protocols in the case of the texture were used. Looking for the best frying conditions, an analysis of response surface optimization process was performed. Results: saddle points were obtained on optimization analysis of the three response variables. A higher time of 550s and between 40 and 80°C, and times 200 to 500s and ∆T 80 to 100°C, zones of influence of moisture content with a value of 0.25% occurred. For the fat content was observed that values below about 20°C and 200s of time and pressures greater than 55kPa, begin to generate relatively low values. Regarding the hardness, treatments 7 and 11 were the most accepted sensorially. Conclusions: The moisture content did not depend on the pressure variable in the process, only the driving force and time altered the outcome of this variable. Considering the sensory evaluation, it was concluded that the desired value for the moisture content was 0.25%, to the fat content values were between 31 and 36%, and hardness between 6.4 and 9.2N.